Parasitological diagnosis of coriander (Coriandrum sativum L.) marketed in the Municipality of Mossoró, Rio Grande do Norte State, Brazil (Research, Society and Development, 2020)
The objective of the research was to diagnose the presence of parasites in coriander (Coriandrum sativum L.) sold in supermarkets and open markets in the city of Mossoró, State of Rio Grande do Norte. In total, 40 samples of coriander were analyzed, 20 of which were sold at open markets and 20 from supermarkets, in search of parasitic structures using the spontaneous sedimentation technique, followed by microscopic analysis. Four supermarkets and four stalls at an open market were randomly analyzed. Among the 40 samples analyzed, 27.5% (11/40) were positive for parasitological contamination, of which 81.8% (9/11) came from open markets and 18.2% (2/11) supermarkets. Among the positive samples, parasitic structures of the genera Ancylostoma sp., Toxocara sp., and Strongyloides sp. Thus, it is concluded that the results demonstrate that a considerable index of the samples is unsuitable for human consumption, and may cause harm to the health of the consumer.